BIODEGRADATION OF DEADWOOD AND SAWDUST BY WHITE-ROT FUNGI ISOLATED FROM LAGOS AND OGUN STATES, SOUTHWEST NIGERIA - Ojo-Omoniyi, O. A.; Ozeigbe, O.; Ahuekwe, E. F. (International Journal of Research -GRANTHAALAYAH, 2021)
Two varieties of Deadwood, Soil and Sawdust samples recovered from L.G.A., Lagos and , Ado-Odo/ L.G.A., state via aseptic procedures were subjected to microbiological analysis over a period of 3 weeks. fungal and bacterial population found on soil, deadwood and sawdust were isolated, thereafter biochemical characterization of the microbial isolates were conducted following standard and conventional methods. The RB 38 dye assay was used as the scientific evidence for identification of microbial isolates with enzymes. The fungal isolates were: ., , , and Aspergillus . A gram positive bacterial isolate found to be consistent in the two varieties of samples used for this study was identified as it RB 38 dye from blue to green. Future studies using molecular methods is expected to unravel the identities of other bacterial isolates.